2015
DOI: 10.1002/2015ja021077
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of energetic ions flux near the Earth's bow shock

Abstract: A new type of variability in the foreshock and magnetosheath is revealed with the recent energetic particle experiments monitor of electrons and protons (MEP) onboard Spectr‐R spacecraft and solid‐state telescope onboard Time History of Events and Macroscale Interactions during Substorms spacecraft, which have high time resolution. Oscillations of energetic ion fluxes are observed in the broad energy range ∼4–400 keV, with periods 10–30 s, often rather monochromatic waveform and accompanied with magnetic oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
4
1
0
Order By: Relevance
“…This is most visible between t = 460 s and t = 490 s in panel (f), corresponding to a period of about 30 s, but a modulation at a shorter period, around 10 s, may also be present in panel (h). This variation in the flux of suprathermal ions is similar to that reported by Petrukovich et al (; see in particular Figure 4 of their paper) and is therefore likely caused by the foreshock ULF waves.…”
Section: Resultssupporting
confidence: 90%
“…This is most visible between t = 460 s and t = 490 s in panel (f), corresponding to a period of about 30 s, but a modulation at a shorter period, around 10 s, may also be present in panel (h). This variation in the flux of suprathermal ions is similar to that reported by Petrukovich et al (; see in particular Figure 4 of their paper) and is therefore likely caused by the foreshock ULF waves.…”
Section: Resultssupporting
confidence: 90%
“…This investigation confirms and extends analysis of our previous publication [ Petrukovich et al , ], presenting oscillations of foreshock energetic ion flux in a wide energy range from 4 keV to the first hundreds of keV. The spatial scale of correlations and the frequency dependence on local magnetic field suggest that these oscillations correspond to previously described 30 s magnetic waves [ Greenstadt et al , ; Le and Russell , ].…”
Section: Discussionsupporting
confidence: 91%
“…Magnetic waves in our data set, although rather intense, do not fit the criteria of Hsieh and Shue [], especially that of high ratio of intermediate to minimal eigenvalue of covariance matrix, which determines the quality of a planar elliptically polarized wave. Magnetic variations in our events look nonlinear (Figure ) [ Petrukovich et al , , Figure 3] and often similar to the shocklet type [ Greenstadt et al , ]. Regi et al [] also suggested that waves are “less monochromatic” (more noisy), when solar wind speed is higher.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The modulation was visible both in the distribution core and in fluxes of suprathermal reflected ions. Such oscillations of enhanced energetic ion fluxes in foreshock observations were also reported by Petrukovich et al (),Petrukovich et al (). The authors discussed the coupling of magnetic field and particle oscillations and suggested that it may be caused by the foreshock ULF waves.…”
Section: Discussionsupporting
confidence: 83%